GC-MS based metabolic profiling of ginger (Z. officinale Rosc.) plantlets - Shapiei, Shazatul Azida; Jameel, Mahdi Harith; Budi Muljono, Julia Retno Andayani (2012)
Introduction and Objective: Ginger (Zingiber officinale Rosc.) is a valuable plant because of wide application in culinary and medicinal uses. Major pungent constituents of ginger rhizomes namely gingerols and their derivatives such as shogaols and paradols are believed to be responsible for most of their pharmacological activities. The proportion of these compounds might vary considerably due to either environmental or genetic factors. In the present study, we intended to do profiling ginger root metabolites of tissue culture-derived plantlets originated from Bukit Tinggi and Sabah using gas chromatography-mass spectrometry.